1999
DOI: 10.1359/jbmr.1999.14.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Characterization of Circulating Osteoprotegerin/Osteoclastogenesis Inhibitory Factor: Increased Serum Concentrations in Postmenopausal Women with Osteoporosis

Abstract: Osteoprotegerin (OPG)/osteoclastogenesis inhibitory factor (OCIF) is a soluble member of the tumor necrosis factor receptor family of proteins and plays an important role in the negative regulation of osteoclastic bone resorption. Whether OPG/OCIF circulates in human blood and how its level changes under pathological conditions is not known. To address these issues, a panel of monoclonal antibodies was generated against recombinant OPG/OCIF and screened for reactivity with solid-phase monomeric and homodimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
220
7
13

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 337 publications
(269 citation statements)
references
References 35 publications
29
220
7
13
Order By: Relevance
“…26 In our hands, the amount of circulating OPG resulted much higher than that reported by others, but it was consistent with the values obtained by using antibodies able to detect both monomeric and homodimeric forms of OPG. 28,29 OPG was significantly lower in neuroblastoma patients than in the healthy children, but no differences were found according to either the stage of disease or the presence of metastasis. The ROC curve analysis showed that all patients had abnormal values, suggesting that OPG measuring could be a useful tool for the differential diagnosis of small round-cell tumors in pediatric age, as well as for the identification of neuroblastoma with unusual presentation.…”
Section: Discussionmentioning
confidence: 67%
“…26 In our hands, the amount of circulating OPG resulted much higher than that reported by others, but it was consistent with the values obtained by using antibodies able to detect both monomeric and homodimeric forms of OPG. 28,29 OPG was significantly lower in neuroblastoma patients than in the healthy children, but no differences were found according to either the stage of disease or the presence of metastasis. The ROC curve analysis showed that all patients had abnormal values, suggesting that OPG measuring could be a useful tool for the differential diagnosis of small round-cell tumors in pediatric age, as well as for the identification of neuroblastoma with unusual presentation.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, breast cancer patients with or without bone metastases had increased OPG levels compared to healthy controls, contrasting with the absence of elevation found by Lipton et al (2002). The reasons for these discrepancies are unclear, but they could be attributed to patient population characteristics and/or specificity of assays for the various circulating forms of OPG (Yano et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Since OPG suppresses bone resorption and increased alkaline phosphatase (Alk-P) activity is associated with bone formation, both of these markers may be elevated during bone anabolism. High serum levels of Alk-P and OPG were reported in a study of high turnover bone disease (Yano et al 1999). However, the nature of the relationship between serum OPG and bone turnover markers following PTX is still debated.…”
mentioning
confidence: 99%